The Evaluation of Hello Snake Game in Learning Java Programming Language - Khai Tick, Voon; Nordin, Noradila (Multidisciplinary Applied Research and Innovation, 2021)
The learning process of Java programming language can be frustrating and cause students to lose their motivation. The idea of the game-based learning approach can promote students' learning attitudes and motivate them during the learning process. The objectives of this study are to identify the requirements, develop and evaluate the usability of Hello Snake, a snake-based online game on learning Java programming language. It uses agile game development cycle that has four phases in discovering, designing, developing, and testing the game. Hello Snake was evaluated by 30 respondents who are currently enrolled as university students, and the game received more than 89% of positive feedback. It is reported that the game interface is easy to navigate, the gameplay is easy to learn, and the game elements are visually appealing with harmonious music. The findings reported that more than half of the respondents had improved their Java programming language skills after attempting the game through tests that were conducted before and after the respondents try the game. The study believes that the Hello Snake can be an alternative learning tool for students and an additional teaching tool as it can improve the students' knowledge of Java programing language.